Gestão do desenvolvimento de curso a distância: investigação sobre a própria prática - Rubim, Lígia Cristina Bada (2011)
The aim of this research is to investigate the relations which emerge from the practice of the management of the processes of development of distance education courses, considering the different elements which directly influence the dynamics they involve. I assume there are no readymade models to be followed since the practice of the management of courses is done based on the concepts of general and distance education, considering the organizational context it happens and also the specific knowledge inherent to the courses of the modality. Taking into consideration the need of reference for the practice and academic writings pointing out new knowledge on the subject, this research presents a relevant social and scientific contribution. The methodological reference of this investigation is based on the value of the experience, the role of reflection and the investigation on one s own practice, in the view of qualitative methodology. The scenario in which this practice was investigated is the one of the development of the distance Lato Sensu Post Graduation course on Entrepreneurial Management at the Center for Applied Technology Education, at Senac São Paulo. I concluded that the practice of the managing of development of courses is composed by the definition of the stages of development, the adoption of the stages as guidelines for the management, the participation on the pedagogical project elaboration, the planning of the guidelines for the preparation of the course materials, the making up of the team and the alignment and acceleration of team work; and such dynamics has been made up of key elements related to the management values, institutional context, area specific knowledge, the characteristics of the course level and to the relation between my views and practice, among others